2002
DOI: 10.1021/ja011261r
|View full text |Cite
|
Sign up to set email alerts
|

Stable [Pb(ROH)N]2+Complexes in the Gas Phase:  Softening the Base To Match the Lewis Acid

Abstract: Experiments have been performed in the gas phase to investigate the stability of complexes of the general form [Pb(ROH)(N)](2+). With water as a solvent, there is no evidence of [Pb(H(2)O)(N)](2+); instead [PbOH(H(2)O)(N-1)](+) is observed, where lead is considered to be held formally in a +2 oxidation state by the formation of a hydroxide core. As the polarizability of the solvating ligands is increased through the use of straight chain alcohols, ROH, solvation of Pb(2+) is observed without proton transfer wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…The preferred elimination of nitric acid at the MS 4 stage might instead suggest that the complex ion has the former composition, and that a proton is transferred from a coordinating alcohol molecule to the nitrate anion during the dissociation reaction. Such a proton transfer process is not without precedent, and has been recently reported for gas-phase alcohol complexes incorporating Pb 2ϩ [47]. The strong tendency to form alkoxide species, noted above, may be a driving force for the apparent proton transfer step and subsequent elimination of HNO 3 .…”
Section: Resultsmentioning
confidence: 81%
“…The preferred elimination of nitric acid at the MS 4 stage might instead suggest that the complex ion has the former composition, and that a proton is transferred from a coordinating alcohol molecule to the nitrate anion during the dissociation reaction. Such a proton transfer process is not without precedent, and has been recently reported for gas-phase alcohol complexes incorporating Pb 2ϩ [47]. The strong tendency to form alkoxide species, noted above, may be a driving force for the apparent proton transfer step and subsequent elimination of HNO 3 .…”
Section: Resultsmentioning
confidence: 81%
“…S19). Many studies have demonstrated the formation of Pb(II)-OH in an aqueous solution of Pb(II) (Supplementary Note S4) [31][32][33][34] . Our experimental studies using Fourier-transform ion cyclotron resonance mass spectrometry, which is a very powerful technique for the structural determination of new compounds with ultra-high mass resolution and accuracy 35,36 , provided further evidence for the existence of the Pb(II)-OH species in the Pb(II) aqueous solution ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This may allow Pb(II) to mediate the initial proton transfer more effectively in the above step. In addition, the lone electron pair (6s 2 ) of Pb (II) may promote the proton transfer 31,32 contributing to its outstanding catalytic performances. These features may explain why Pb(II) demonstrates better catalytic performances for the formation of lactic acid than many other metal ions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21] The gas-phase chemistry of Pb 2 + is less known although a number of species have been experimentally detected. [6,[22][23][24] However, the spectroscopic and theoretical investigations of gas-phase complexes remain surprisingly rare despite available high-level theoretical data. [25] To the best of our knowledge, studies devoted to such species are limited to: PbA C H T U N G T R E N N U N G (H 2 O), PbA C H T U N G T R E N N U N G (HO 2 ), PbOH, PbH 2 , PbO, PbO 2 and PbO 3 .…”
Section: Znmentioning
confidence: 99%